Dental complications and management of patients on bisphosphonate therapy: A review article - Sandeep Kalra; Veena Jain (Journal of Oral Biology and Craniofacial Research)
Bisphosphonates are group of drugs that inhibit bone resorption and are used to treat a range of pathologies including Paget's disease, osteoporosis, multiple myeloma and metastasis associated with breast or prostate cancer. The most common complication in patients on bisphosphonate therapy is osteonecrosis of jaw (ONJ) which can occur after any surgical dental procedure and the risk for the development of osteonecrosis of jaw is higher in patients receiving intravenous bisphosphonate therapy than in patients receiving oral bisphosphonate therapy. Typical presentation is in the form of non-extraction socket, presence of exposed bone, gingival swelling or purulent discharge, when local debridement and antibiotics are ineffective.At present, there is no effective treatment for bisphosphonate induced osteonecrosis, so prevention is extremely important. Maximum precautions should be taken in patients who are at the risk of development of ONJ especially when any dental surgical procedure like extractions, retrograde apicoectomies, periodontal surgery and implant placement is contemplated. Dentists and oral or maxillofacial surgeon must keep up to date with the latest approaches or guidelines to prevention and the risk factors, particularly when treating patients who are on bisphosphonates, or who will be taking bisphosphonates.